The effect of the cationic polyelectrolytes on the crystallization of sodium perborate tetrahydrate - SARGUT, SİBEL (SOC CHEMICAL ENG JAPAN, 2004)
Effect of the cationic polyelectrolytes on sodium perborate crystallization in the presence of 2.5% excess sodium metaborate concentration has been studied in an MSMPR type reaction crystallizer. Polyelectrolytes, which are in various charge densities but in the same chemical composition, have been used in the experiments. Cationic polyelectrolytes affected the SPT crystallization by its non-ionic adsorption mechanism. It has proven that the polyelectrolyte having 2% cationicity has affected the quality of sodium perborate tetrahydrate (SPT) crystallization positively. Increasing the cationicity leads to reversing the effect on a product quality change with the cationicity of polyelectrolytes. Polyelectrolytes having 2% cationicity can be used to smooth the shape of crystals and to increase the mechanical strength, the bulk density and the average particle size in SPT crystallization.
Keywords: sodium perborate; crystallization kinetics; surface potential; polyelectrolytes; bulk density; attrition rate; AQUEOUS-SOLUTIONS; CRYSTAL-GROWTH; DISSOLUTION